Voltage‐Modulated Untwist Deformations and Multispectral Optical Effects from Ion Intercalation into Chiral Ceramic Nanoparticles (Adv. Mater. 16/2023). Issue 16 (20th April 2023) - Shao, Xiao; Zhu, Cheng; Kumar, Prashant; Wang, Yanan; Lu, Jun; Cha, Minjeong; Yao, Lin; Cao, Yuan; Mao, Xiaoming; Heinz, Hendrik; Kotov, Nicholas A.
Abstract : Chiral Ceramic Nanoparticles In article number 2206956, Hendrik Heinz, Nicholas A. Kotov, and co‐workers describe how the chirality of V2 O3 nanoparticles strongly changes when they intercalate Zn 2+ ions, generating strong modulation f polarization rotation from the ultraviolet to infrared range. High g ‐factors, synthetic simplicity, and environmental robustness of self‐assembled composite films from chiral V2 O3 nanoparticles provide a versatile platform for photonic devices.